RE-DESAIN KARTON BOX PADA KEMASAN BAG IN BOX (BIB) COKELAT CAIR MENGGUNAKAN METODE DFSS UNTUK KEAMANAN PRODUK PERUSAHAAN COKELAT GRESIK - Bagus Arif Rahman (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Gresik Chocolate Company is a food company with the main product of liquid chocolate. This research will focus on products with BIB packaging because, Gresik Chocolate Company in March-June there were 294 BIB carton boxes returned by the customer and there were 167 BIB carton boxes that were found defective or unfit for delivery in the warehouse storage area. In this study, the technique used was Design For Six Sigma with DMADV approach. In this study the tools used are control charts, cause and effect diagrams, and pareto diagrams. DMADV (Define, Measure, Analyze, Design, and Verify) is a methodology for designing and improving new services, products or processes. After re-design and taking checking samples using pareto charts when analyzing the results of new design verification, from 327 sample boxes calculated defect data 77 units or 23% defective carton boxes before re-design to 8 units or 2.4% defective carton boxes after re-design. The implementation of the DFSS method with the DMADV approach proved effective in replanning the BIB carton box design. Because it succeeded in making an optimal design by eliminating 4 types of defects in carton boxes based on VOC to 0. We recommend that companies provide clear SOPs and regular training for operators to better understand and be aware of the potential dangers that cause product defects.